Hidrogeoquímica do fluoreto em porção da zona de afloramentos do Sistema Aquífero Guarani na região central do estado do Rio Grande do Sul - Luiz, Thiago Boeno Patricio (2017)
This work investigated the hydrogeochemical behavior of groundwater with fluoride (F-) anomalies and its association with hydrochemical types in a portion of the Outcrop Zone (OZ) of the Guarani Aquifer System (GAS). The selected area for the research comprised the Restinga Seca, Agudo, Paraíso do Sul and Novo Cabrais municipalities, in an area of approximately 2,034 km², located in the Central Depression of the Rio Grande do Sul State, southern of Brazil. From the compilation and collect of hydrochemical data, the study presents an approach that uses the integration of geostatistical and geochemical analyzes, aiming at the identification and quantification of phenomena that may be interfering in the groundwater chemistry. In this context, hydrogeochemical modeling was performed using the PHREEQC 3.3.5 modeling code, looking for signs of mineral saturation and its relation with the ionic strength. Thus, it was observed that the occurrences of fluoride anomalies in the municipalities of the study area are highly salinized (due to increases in sodium, chloride and sulfate concentrations). The hydrochemical classification has predominance of sodium chlorate waters followed by sodium sulphates and bicarbonated sulphate sodium chlorate. For total boron and bromine parameters, evaluated by inductively coupled plasma optical emission spectrometry (ICP-OES), significant concentrations were identified for these elements and boron showed a positive statistical correlation with fluoride. The analysis of groundwater flow along with the morphostructural tracing of lineaments allowed to evaluate the occurrence of large tectonic blocks formed by the Vacacaí, Vacacaí-Mirim and Jacuí rivers, with a rigid tectonic control with predominant lineaments according to the directions N-60-70-E and N-20-50-W. The results were analyzed by the main directions of flow and lineage, which allowed to determine characteristics of mineral dissolution of carbonate rocks until their saturation, where they can be precipitating in the underground environment where the water is more salinized. The halite and silvite halides showed dissolution tendencies along the traced transects, towards the mineral equilibrium. The fluorite mineral, in turn, presented subsaturation with tendencies to mineral equilibrium, and possibly, precipitation in the most salinized waters. The applied methodology allowed to extract information for a better understanding of the hydrogeochemical dynamics of salinized waters and their water/rock interactions in the OZ portion of the GAS, therefore, constituting, as a material to support the research of anomalous fluoride concentrations in groundwater and to practices of management of this important aquifer system.